Planktonic foraminiferal ecozones: response of the pelagic environment to palaeoclimatic changes in the eastern Mediterranean Sea - DRINIA, H.; ANTONARAKOU, A.; DERMITZAKIS, M. (Mediterranean Marine Science, 2003)
A detailed study of the planktonic environment of the eastern Mediterranean Sea has permitted the reconstruction of the climatic history of this part of the basin during the time span from 9.7 to 6.6 Ma. The eastern Mediterranean Sea is confirmed as having a strong sensitivity to the climatic changes that occurred during that timespan. One of the very few complete hemipelagic successions of the Upper Miocene in Mediterranean is found in Gavdos island (SW Crete). Quantitative and qualitative modifications of the planktonic foraminiferal communities observed in Metochia section exhibit a sequence of biological events summarized in 11 successive main time intervals. The bioevents are defined by frequency peaks and/or local (re)-occurrences or (temporary) disappearances of some of the taxa, in association with more or less important fluctuations of the more common species. The planktonic foraminifera show a strong correlation with sea surface temperature variations and with changes in the physical and chemical properties of the upper water column caused by the climatic instability. Two prominent shifts in faunal parameters divide the period recorded in Metochia section into three major time slices that are discussed in chronological order: a cooling trend from 9,7 to 7,6 Ma, a warmer period from 7,6 to 7,2 Ma and then a cooling trend which finishes at the Messinian.